Assessing the Skill Sets from the NEP Policy 2020: Scale Development and Validation - M., Spoorthy Reddy; V., Pavithra; Thomas, Mary Rani (Prabandhan: Indian Journal of Management, 2024)
Purpose : The central aspect of this paper is the National Education Policy (NEP) 2020, an education-based policy in the Indian context. The article captured the opportunities from the perspective of the skill set it offers to its important stakeholders, students; the current research has aimed to propose and validate an instrument to measure the skill set identified from the NEP document and academic expertise, which could be used to measure students’ skill-based performance. Design/Methodology/Approach : The first section used EFA to establish four skill sets: Employability Skills, Communal-Based Skills, Social and Emotional Skills, and Individualistic Skills. The CFA model was further deployed to confirm the factors; the study was administered to a sample of 820 students from various commerce and management colleges from South and North Bangalore. Findings : The research results could be applied to evaluate the effectiveness of skill sets on students’ performance to create holistic education. Originality : The first step is to develop and validate scales for measuring skill sets under NEP 2020. Second, in accordance with the pupils’ order of priority, to close the gap between the talents stated and those observed. Research Limitations/Implications : The study was conducted only with students of commerce and management disciplines in Bangalore. Practical Implications : NEP has placed a greater emphasis on competency development and skill enhancement, which aids in the development of higher-order cognitive, social-emotional, and 21st-century abilities necessary for employment in the future. NEP gave greater autonomy to students to choose their learning pathway and develop skill sets, which are likely to make them job creators, thereby giving rise to the entrepreneurial culture. Social Implications : To cultivate an aspirational student body, it is critical to instill the necessary skill sets in pupils. Policymakers and decision-makers could then organize their courses using these skill sets.